2. Characterization Of Lactic Acid Bacteria (LAB) Origin Sumatran Orangutan (Pongo abelii) In Zoo Bukittinggi Based On Analysis 16 S rRNA - Siti Hajar; Safika Safika; Darmawi Darmawi; Wenny Novita Sari; Erdiansyah Rahmi; Yandi Syahputra; Nurliana Nurliana; Rinidar Rinidar (The International Journal of Tropical Veterinary and Biomedical Research, 2016)
The purpose of this study was to characterize the bacterial 16S rRNA gene of Sumatran orangutan (Pongo abelii) Bukittinggi West Sumatera zoo. The sample used in this study are lactic acid bacteria of the Sumatran orangutan (Pongo abelii) derived from zoo Bukittinggi West Sumatra Indonesia. This study was an exploratory study that conducted at the Laboratory through several stages. The first stage was the isolation of LAB from faeces of Sumatran orangutans using MRS agar medium and then cultured in a liquid medium NB. The next stage was the isolation of total DNA, and then, the third stage was the amplification of the 16S rRNA gene and agarose gel electrophoresis. Then,in the fourth stage of determining the DNA sequence and analysis of DNA sequence homology. The final stage was the computational analysis of 16S rRNA gene Sumatran orangutan (Pongo abelii). The results showed that lactic acid bacteria (LAB) from the Sumatran orangutan (Pongo abelii) is close to lactic acid bacteria Lactobacillus helveticus strain IMAU50151 with the levelof similarity of 89%. It is possible that these bacteria is a new species or the species that LAB has not been reported in Genbank.